Project-Based Learning Model To Develop Business Management Capabilities - Suharsono, Naswan; Hidayat, Rahmat; Zen, Fadia; Juariyah, Lohana (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This research was conducted to produce a project-based learning model with three variations of business activities and its five components in an integrated manner to improve the ability to manage a business. The output to be achieved with this model is the strengthening of entrepreneurial character, improvement of operational capabilities and strengthening of managerial capabilities, as well as business development through improving product quality and expanding access to digital markets. The design used is research and development (R&D), starting from the analysis of entrepreneurial needs, determining components and making product prototypes, testing and revising, continuing to implementation. Data on increasing managerial and operational abilities, changes in self-character, as well as business development data for the 30 student entrepreneurs and alumni were analyzed descriptively. The efforts to improve the ability to manage business and the ability to capture market opportunities are analyzed by SWOT and t-test. Data analyses by using descriptive view show that operational skills and managerial abilities can be improved by utilizing feedback information from interactions with expert teams, colleagues on campus and alumni groups in the field. The results of the data analysis show that the developed model has been successfully implemented in the field to achieve the proposed competency standard. The results of data analysis show that the ability to manage a business develops in a sustainable manner, with variations in acceleration that vary according to the type of business chosen, as well as internal and external factors that influence the business.